Political responsibility and global health. Issue 3 (4th March 2018) - Poku, Nana K.; Sundewall, Jesper
Abstract: Globalising dynamics have had wide-ranging and pervasive impacts on nearly every form of human relatedness, which now include the bases upon which states calculate and express their political responsibilities. As the 'reach' of practical and normative pressures extends and their demands intensify, the compass of state responsibility is becoming a key pressure point for facing the challenges and mediating the tensions of our globalised and still globalising world. This theme is examined from a global health perspective. The general disposition of states toward their acknowledged political responsibilities is unlikely to change, but the combination of legal, normative, political and practical dynamics impinging on them have already begun to register, as both states and the international system adjust to a politics that now have global dimensions.